Racial Isolation and Marginalization of Economic Research on Race and Crime - Mason, Patrick L.; Myers, Samuel L.; Simms, Margaret (Journal of Economic Literature, 2022)
This essay examines the extent to which research on the economics of race and crime produced by Black economists or published in the flagship journal of the organization of Black economists, the Review of Black Political Economy (RBPE), is undervalued by mainstream economics. We use modern bibliometric methods to test for citation biases in the economics of crime literature. We also identify the contributions of three streams of research overlooked in the mainstream literature: identity, police use of force, and mass incarceration. We find evidence that Blacks publishing on race and crime in top economics journals are less likely to be cited than non-Blacks and that articles published in the RBPE are less likely to be cited than articles published in other journals. A review of some under-cited articles reveals that themes related to identity, police use of force, and mass incarceration hold valuable insights for policy makers and those seeking solutions to problems of persistent racial disparities in the criminal legal system. (JEL A11, A14, H75, J15, K42)